Sala de aula virtual invertida e abordagem investigativa : produção de sequências didáticas no ensino de genética mendeliana e sistema ABO - Santos, Xisda Magna Rafaski dos (2020)
The Genetics Teaching of High School (HS) is fascinating and at the same time challenging for both biology teachers and students because it is a content difficult to understand due to its high degree of abstraction and complexity. Using methodologies that attracted students' attention and support teacher praxis can contribute to this process. Thus, the aim of this research was analyze the methodological potential of the reversed virtual classroom with an investigative approach in the teaching-learning process of high school Genetics Classes. For the reversal of classes with an investigative approach, students previously studied concepts and theories posted in the form of videos, abstracts and images making use the schoology platform promoting the use of digital information and communication technologies (DICT) as a virtual learning classroom. In the traditional environment, the classes were performed in the classroom and biology laboratory and dedicated to the realization of collective activities such as exercise resolution, experimentation, model production and simulation. The contents used for the production of the 3 didactic sequences (DSs) were Basic Concepts and Foundations of Genetics, Mendel’s First Law and Multiple Alleles (ABO system), applied in two classes of 2nd grade appertaining to HS based on a state public school in the city of Serra - ES. The methodological approach was quantitative and qualitative, action research method, and the data were collected through participant observation, activity records, pre- and post-class along with methodological diagnostic questionnaires. The students participated enthusiastically and committed, showing excellent acceptance of virtual classes, especially in face-to-face classes. The results were satisfactory because it was noticeable over the analyses the growth of students in discussions, interactions, autonomy, criticality and involvement in the various stages of the methodological process. The methodology presented negative points, however the positive points were more expressive and all these results allowed to deduce that active methodologies such as the reversal virtual classroom associated with the investigative approach is an excellent proposal to work on the Teaching of Genetics